Gambaran Program Makanan Bergizi Gratis (Mbg) Ditinjau dari Aspek Pelaksanaan dan Kepuasan Siswa Sekolah Menengah Pertama - Luluk Hilda Kusumarini; Sri Wahyuni Ningsih; Mirza Fathan Fuadi (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
The Free Nutritious Meal Program (MBG) is one of the government’s strategic policies aimed at improving students’ nutritional status and learning quality, particularly at the junior high school level. Early adolescence, aged 13–15 years, is a critical growth period that requires optimal nutritional intake, while national surveys still indicate deficiencies in energy and protein intake among this age group. This study aims to describe the implementation of the MBG Program and the level of student satisfaction as direct beneficiaries. The research employed a quantitative descriptive design conducted over one month in the working area of SPPG Yayasan Bina Bangsa Semarang, Gunungpati, Semarang City. The sample consisted of 101 junior high school students selected using purposive sampling techniques. Data were collected through structured questionnaires covering program implementation and student satisfaction aspects. The findings revealed that most students assessed the program implementation as high to very high. Student satisfaction was also categorized as high, particularly regarding food quality, portion adequacy, cleanliness, safety, and service. The MBG Program was considered effective in improving learning concentration, reducing unhealthy snacking habits, and encouraging healthy eating patterns. This study concludes that the MBG Program has been implemented effectively and is relevant in supporting sustainable improvements in students’ nutritional status and educational quality.